2023
DOI: 10.1038/s41598-023-45857-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform failure and differential pressure relief technology of roadway under irregular goafs in deep close-distance coal seams

Shuaifeng Yin,
Xinjian Zheng,
En Wang
et al.

Abstract: In response to the control problems of large-deformation roadways in close-distance coal seams, taking a typical roadway under irregular goafs and residual coal pillar in deep close-distance coal seams as the background, the characteristics of mine pressure and key difficulties in surrounding rock control of roadway are explored and an improvement strategy for controlling surrounding rock is proposed. The stress expression in roadway floor under the influence of residual coal pillar is derived by theoretical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Long-term research and production practice have shown that after mining the working face, the movement and destruction space of the overlying rock in the goaf presents a “trapezoidal” shape 10 12 . When using the strike-long wall complete collapse method for coal mining, due to the length of the working face being much smaller than its mining length, a large number of section coal pillars are left in the goaf along the inclined direction of the coal seam after mining 13 15 , due to the influence of the remaining coal pillars, the non-subsidence area, sufficient settlement area, and non-sufficient subsidence area of the overlying rock alternate. The coal seams waiting for upward mining exhibit uneven settlement characteristics in the form of waves in space.…”
Section: Methods For Determining the Reasonable Layout Parameters Of ...mentioning
confidence: 99%
“…Long-term research and production practice have shown that after mining the working face, the movement and destruction space of the overlying rock in the goaf presents a “trapezoidal” shape 10 12 . When using the strike-long wall complete collapse method for coal mining, due to the length of the working face being much smaller than its mining length, a large number of section coal pillars are left in the goaf along the inclined direction of the coal seam after mining 13 15 , due to the influence of the remaining coal pillars, the non-subsidence area, sufficient settlement area, and non-sufficient subsidence area of the overlying rock alternate. The coal seams waiting for upward mining exhibit uneven settlement characteristics in the form of waves in space.…”
Section: Methods For Determining the Reasonable Layout Parameters Of ...mentioning
confidence: 99%
“…used as the constitutive model for the deformation and failure of roadway surrounding rock. Te mechanical parameters of the numerical model are calculated using the Hoek-Brown criterion [39,40]. Te anchor cable is simulated using a cable element.…”
Section: Numerical Simulation Analysis Of Roadway Stability Under Anc...mentioning
confidence: 99%
“…In the treatment of mine fire, techniques such as yellow mud injection, inert gas injection, and loess covering are generally adopted. With the development of science and technology, mine fire prevention and control technology continue to progress. Such as three-phase foam as the representative of the foam class fire prevention materials, as well as the colloid as the representative of the colloid fire prevention materials gradually into the field of vision, the field application effect is remarkable. , Regarding research on coal pillars, most scholars at home and abroad focus on the mechanical characteristics and fragmentation mechanism of coal pillars. However, it is worth noting that coal pillar cracks, under the influence of underground formation pressure, would further develop and result in a large number of air leakage channels. Besides, air circulation caused by the atmospheric pressure difference on both sides of coal pillars may also accelerate the spontaneous combustion of fragmented coal in coal pillars. , Under the guidance of safety-related coefficient criteria and safety principles, Tang divided the narrow coal pillar and the goaf into “safe zone”, “general zone”, and “dangerous zone”, according to two indicators, i.e., the permeability of the narrow coal pillar and the spontaneous combustion risk of residual coal in the goaf .…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 Regarding research on coal pillars, most scholars at home and abroad focus on the mechanical characteristics and fragmentation mechanism of coal pillars. 16 19 However, it is worth noting that coal pillar cracks, under the influence of underground formation pressure, would further develop and result in a large number of air leakage channels. Besides, air circulation caused by the atmospheric pressure difference on both sides of coal pillars may also accelerate the spontaneous combustion of fragmented coal in coal pillars.…”
Section: Introductionmentioning
confidence: 99%